Mating type and genetic diversity analysis of Pyricularia oryzae collected from Thai rice varieties - Tansian, P.; Parinthawong, N. (My University, 2018)
Rice blast disease caused by Pyricularia oryzae, is one of the most damaged of rice production worldwide. The fungi are a great diversity on both genotype and pathotype. The genetic relationship of P. oryzae collected in Thailand during year 2016 and 2017 was analyzed. Rice plants appeared blast symptom were collected from epidemic areas and was isolated by single spore. All isolates were identified for mating type using MAT1-1 and MAT1-2 primer sets. In this result, the mating type MAT1-2 was mostly found in Thailand and only about 7.7 % of MAT1-1 was found in the population. In this observation, both MAT1-1 and MAT1-2 were found from isolates collected from the same location in Phetchabun province. Therefore, the genetic analysis of 14 Magnaporthe grisea using microsatellite (MGM) markers was cluster-analyzed using UPGMA method of the SHAN program. The result showed cluster analysis was separated the population into 11 groups. Group 1 to 7 showed the percentage of the population with 3.8, 5.8, 36.5, 13.5, 3.8, 25.1 and 3.8, respectively. For group 8-11, the rice blast pathogen from North and South of Thailand were separated into single isolate group. Group 6 was the highest diversity of province numbers which obtained from diverse rice varieties that showed similar genotype but difference in pathogenicity. The difference isolates of fungi could infect the same rice variety. Genetic diversity and determination of mating type of rice blast populations in Thailand are needed to study and useful for predicting an epidemic of rice blast disease and selecting the appropriate isolates for blast breeding programs.
Keywords: Genetic diversity analysis; Magnaporthe grisea microsatellite (MGM) markers; Pyricularia oryzae; Rice blast disease